1986
DOI: 10.1093/oxfordjournals.aje.a114304
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Ovarian Cancer Risk

Abstract: To study the influence of alcohol consumption on the risk of ovarian cancer in women under age 55, the authors examined data collected in a multicenter, population-based case-control study--the Centers for Disease Control's Cancer and Steroid Hormone Study. Between August 1981 and December 1982, 433 women 20-54 years of age with newly diagnosed ovarian cancer and 2,915 women 20-54 years of age selected at random from the same geographic areas were asked about their consumption of alcoholic beverages during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
1
30
2
Order By: Relevance
“…We could not confirm the positive associations of either alcohol consumption (17,21) or coffee consumption (18) with ovarian cancer, which have been reported previously. Studies on the role of dietary fat have been inconclusive; one report showed a significant association (20) while another did not (19).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…We could not confirm the positive associations of either alcohol consumption (17,21) or coffee consumption (18) with ovarian cancer, which have been reported previously. Studies on the role of dietary fat have been inconclusive; one report showed a significant association (20) while another did not (19).…”
Section: Discussioncontrasting
confidence: 95%
“…We conducted a case-control study of ovarian cancer in Japan designed to evaluate reproductive (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), genetic (5,7,9,12,17), and dietary risk factors (17)(18)(19)(20)(21), all of which have been found to be associated with the occurrence of ovarian cancer in Western countries.…”
mentioning
confidence: 99%
“…That this association was limited to the period of time shortly before diagnosis suggests that it is related to growth rather than initiation of these tumours. Alcohol consumption has been reported as unassociated with epithelial ovarian cancer (Gwinn et al, 1986), and an association with testicular cancer has not been reported. Alcohol use may, however, increase the risk of breast cancer and other cancers (Schatzkin et al, 1987).…”
Section: Discussionmentioning
confidence: 98%
“…2,6,23 Bias related to control selection is a particular concern in hospital-based studies given that many diseases leading to hospitalization are also associated with alcohol use. Of population-based case-control studies, several suggested nonsignificant 5,14,24 or significant 16 protection, whereas the remainder were consistent with an increased risk 8 or no association. 11,15 Only 2 prospective studies have considered the association: null results were obtained in the Netherlands Cohort Study, 13 whereas the Iowa Women's Health Study indicated a statistically significant inverse trend with increasing intake.…”
Section: Discussionmentioning
confidence: 99%